2018
DOI: 10.1159/000491701
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Scrambled-Sentences Task to Assess “Shattered Assumptions:” Construction of the Test and Investigation of Neural Substrates in an fMRI Study

Abstract: Background: Increasing recognition is being given to the importance of cognitions observed in posttraumatic conditions. These cognitions may reflect the activation of negative schemas. The aim of this work was to evaluate the feasibility of the scrambled-sentences task (SST) to assess individual differences in attributions commonly observed after traumas. Originally developed to assess the tendency to activate negative cognitions in individuals predisposed to depression, the SST is a laboratory task the outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Although conceived at the time in terms of the failure of control processes in preventing negative content to prevail (Wenzlaff & Wegner, 2000), it has become increasingly difficult to sustain this original model. Neuroimaging studies, which have been very consistent, show no trace of increased recruitment of cortical substrates of executive function in the SST or of an association with individual differences in working memory capacity (Viviani et al, 2010;Viviani, Mahler, et al, 2018). However, it would be equally difficult to attribute selection of sentences in the SST to an automatic process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although conceived at the time in terms of the failure of control processes in preventing negative content to prevail (Wenzlaff & Wegner, 2000), it has become increasingly difficult to sustain this original model. Neuroimaging studies, which have been very consistent, show no trace of increased recruitment of cortical substrates of executive function in the SST or of an association with individual differences in working memory capacity (Viviani et al, 2010;Viviani, Mahler, et al, 2018). However, it would be equally difficult to attribute selection of sentences in the SST to an automatic process.…”
Section: Discussionmentioning
confidence: 98%
“…In study 3 (N = 194), we developed a new battery of sentences (30 sentences) by expanding the pool of sentences of previous studies (Viviani et al, 2010;Viviani, Mahler, et al, 2018). Each sentence in this revised battery came with an additional neutral/uncharacterized target word (for example, 'the future is bright/dismal/distant).…”
Section: Study 3: Differential Effect Of Negative and Positive Word T...mentioning
confidence: 99%
“…To summarize, results on the SST's validity are mostly as expected, and mirror those of the earlier study in the context of negative life events. That is, Viviani, Mahler, et al, (2018) found that the SST was highly correlated with measures of PTSD-related DAs such as the PTCI, however, the association with depression was also strong. Further, our results are in line with those of a recent systematic review investigating the psychometric properties of the SST (Würtz, Zahler, et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…To summarize, results on the SST’s psychometric properties are mostly as expected and mirror those of the earlier study in the context of negative life events. That is, Viviani, Mahler et al (2018) found that the SST was highly correlated with measures of PTSD-related DAs such as the PTCI; however, the association with depression was also strong. Further, our results are in line with those of a recent meta-analysis investigating the psychometric properties of the SST (Würtz et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…Moving in a more trauma-related direction, the SST has also been successfully adapted to assess DAs in the context of negative life events (Viviani, Mahler et al, 2018). In the study by Viviani et al, the SST score was associated with questionnaire measures of DAs related to the event and symptoms of depression.…”
mentioning
confidence: 99%